MODEL MATEMATIK ANGKUTAN LIMBAH PADA SALURAN TERBUKA - Didik Purwantoro (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2006)
This research is aimed to know the process of waste transportation on theopen-channel using numerical model. This model is chosen because of some reasons, for example the complication of the river tissue, the influence of ebb which causes difficulty to conduct analytical problem solving. The other excess of this numerical model is cheaper and easier than conducting measurement of waste rate in the field.The equa~on of waste transportation can be formulated as the two physics phenomenon, Le. advection and diffusion process or long dispersion of river. In the solving of equation of waste transportation, each of the components was analyzed separately. The advection part was done first, and the diffusion part was finished then. The advection equation was done using Lagrange interpolation, and the diffusion equation was done using differential method to explicit scheme.The result of the research shows that the use of Lagrange interpolation upto order 4 is still be good enough to finish advection equation for numberCourant 1, 0,75 and 0,5. For number Courant 0.25, numerical mistake causingconcentration degradation of 2.3 0/0. In the diffusion equation, the result of computationusing differential method up to explicit scheme yielding degradation ofwaste concentration from 10 gr/I become 4,96 gr/I for the diffusion coefficient ofKx =10 m2/sc and become 3,73 gr/I for the diffusion coefficient of Kx = 20 m2/sc.